Seminar dan Pelatihan Dasar Public Speaking sebagai Interpersonal Skill Siswa SMK Saintek Nurul Muslimin - Ririn Uke Saraswati; Suripto Moh. Zulkifli; Satim Hamid; Vina Aprilia Anjani; Rizky Ramadhan; Fatimah Az-Zahra; Muhammad Arif Febriyanto; Muhamad Daman Ardian (BADAN PENERBIT STIEPARI PRESS, 2025)
Public speaking is one of the essential interpersonal skills that must be possessed to compete in both the professional and entrepreneurial world, especially for the younger generation. Based on observations, many students still lack confidence when speaking in public, including students of SMK Saintek Nurul Muslimin. The seminar and training activity themed